Genetic diversity among black cumin (Nigella sativa L.) accessions based on quantitative and qualitative traits - Solomon Kassaye Ejigu; Wosene Gebreselassie Abtew; Ermias Lulekal Molla (Agrosystems, Geosciences & Environment, 2025)
Abstract To investigate the genetic diversity in black cumin (Nigella sativa L.), a total of 64 genotypes were tested in an 8 × 8 simple lattice design at Sirinika Agricultural Research Center for two consecutive years during 2022/2023 and 2023/2024. Analysis of variance revealed the presence of significant difference among the genotypes for all quantitative traits except capsule length and diameter. The variation of the genotypes for seed yield was between 0.66 and 1.69 t ha−1 with a mean of 1.02 t ha−1. The genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) for 16 traits are estimated in the range between 3.81% and 49.84% and 6.50% and 50.90%, respectively. H2 and advance as percentage of mean (GAM) ranged from 19.18 to 98.25 and 4.67% and 100.70%, respectively. High to moderate estimates of GCV, PCV, H2, and GAM were observed for all parameters except days to bud formation, days to maturity, capsule length, and capsule diameter. Seed yield showed positive and significant correlation with almost all parameters. The first five PCAs accounted for 72% of the total variability, in which PCA1 contributed 32% and PCA2, PCA3, PCA4, and PCA5 exhibited 13%, 12%, 8%, and 7% contributions to the total variability, respectively. The qualitative data showed high variability except flower color, plant growth type, and stem hairiness. The cluster analysis for qualitative traits was classified into five groups. The research results clearly showed that there was sufficient diversity among the genotypes, which can be exploited for the future black cumin improvement program.